Prospective validation of the Saldías predictive index in community-acquired pneumonia - Calderón Gerstein, Walter (2007)
Introducction: the early identiﬁcation and determinacion of the severity of the disease are of vital importance in the management of patients with community- acquired pneumonia (CAP). Objetive: no prospective studies evaluating the validity of the Saldías Index exist in Perú; an attempt was made to determine the precision of the complex and simple Saldías Indices in the prediction of mortality in CAP. Materials and methods: This is a prospective study, developed from april 2001 to october 2002, in the Hospital Alberto Sabogal of Bellavista, Callao. 152 adult patients with CAP, conﬁrmed by chest x-rays, were included. All the patients were followed to Hospital release or death. Results: The mean age of the participants was 72,8 years. 36,8% of the patients died; the main causes of death were septic shock (27,2%) and multiple organ failure (22,7%). There was no signiﬁcant difference (p = 0,203) between deceased and surviving patients when using the complex Saldías index. The positive predictive value (PPV) for mortality in category IV of the index was only 46.2%. According to the simple Saldías index the survivors had a mean score of 13,04, lower than the 16,59 found in the non survivors. The difference was signiﬁcant (p = 0,000). 77,8% of the patients in category III of the simple index died, as opposed to 25,3 % in category I. The PPV for mortality in patients in category IV was 77,8% with an Odds Ratio of 7,67 (95% CI: 2,48 – 22,45) and a speciﬁcity of 95,8%, as opposed to category I with an Odds Ratio ratio under 1 (OR = 0,287, 95% CI: 0,14 - 0,57), but with a low negative predictive value. Conclusions: The complex Saldías index was not useful to evaluate the mortality risk in CAP. The simple Saldías index predicts mortality adequately but not survival; it is less precise and more complex than the CURB-65 and CRB-65 indices.